Occupational Health and Safety Animated Learning Videos: Validity and Feasibility - Arthur, Riyan; Anisah, Anisah; Wijayanti, Ima; Sidik, Jaelani (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to produce animation learning media on OHS courses with the help of software. This research uses Lee & Owens development research model. This research is done through 5 stages, namely assessment or analysis, design, development, implementation, evaluation. This research uses questionnaires to test the feasibility of learning media products through the validation of material experts and media experts. Assessments from students using scale instruments designed for validation of experts, materials, students, and construction skilled workers. Learning media products in the form of five animated videos. The rating by media experts of 87.13% is considered highly feasible. The assessment by the material expert scored at 81.43 which is categorized as very feasible. Assessments by students through limited trials scored 85, 86% of which were categorized as highly feasible. Assessments by construction skilled workers through limited trials get a value of 87% which is also categorized as highly feasible.